Morphometric analysis of structural arrangement of the testial arteries in postresectional arterial pulmonary hypertension - S. O. Konovalenko (Kazimierz Wielki University, 2020)
Introduction. Removal of the right or left lung can lead to postresection pulmonary arterial hypertension, venous stasis in the organs of the great circle of blood circulation and structural and functional changes in them. Morphological changes in endothelial cells of arteries of testes in postresection pulmonary arterial hypertension are insufficiently studied. Objective of the research: to study features of structural reorganization of testicular arteries at postresection pulmonary arterial hypertension. Materials of the research and their discussion. Morphological methods were used to study the structural rearrangement of the testicular arteries of 40 rats, which were divided into 3 groups. The 1st group included 11 intact animals, the 2nd - 19 rats with arterial hypertension in the small circulation and compensated pulmonary heart, the 3rd - 10 experimental animals with pulmonary arterial hypertension and decompensated pulmonary heart. Postresection pulmonary arterial hypertension and pulmonary heart were modeled by performing right pulmonectomy in rats. One month after the start of the experiment, rats were euthanized by bloodletting under conditions of thiopental anesthesia. A separate weighing of the chambers of the heart, their planimetry. Pieces were cut from the testicles, which were fixed in 10% formalin solution, passed through ethyl alcohols of increasing concentration and placed in paraffin. Microtome sections after dewaxing were stained with different dyes. In the left and right testes, the outer and inner diameters of small-caliber arteries, media thickness, Kernogan index, endothelial cell height, diameter of their nuclei, nuclear-cytoplasmic ratios in endotheliocytes, and relative volume of damaged cells were measured. Quantitative indicators were processed statistically. Results of the research and their discussion. Morphometrically, it was found that with decompensation of the postresection pulmonary heart, the lumen of the small-caliber arteries of the left testicle decreased by 12.6 %. the Kernogan index - by 11.7 %, and the right - by 9.5 and 9.9 %, respectively. The relative volume of damaged endothelial cells of the studied vessels in right ventricular failure increased 11.6 times, and the right - 9.3 times. Histological examination of the testicles micropreparations of experimental animals after right-sided pulmonectomy showed severe vascular disorders (plethora of mostly venous vessels of the microhemocirculatory tract, stasis, thrombosis, diapedetic perivasal hemorrhage), stromal and perivasal edema, noncystic edema, dystrophy, dystrophy. Conclusions. It is established that in the conditions of the simulated pathology the wall thickens markedly, the lumen of the studied arteries narrows, endotheliocytes are damaged, structural cellular homeostasis is disturbed, which is complicated by their dysfunction, deterioration of blood supply, hypoxia, dystrophic, necrobiotic lesions. Structural changes in the arteries predominated in the left testis and in pulmonary heart decompensation.